Nasopharyngeal carcinoma-associated inflammatory cytokines: ongoing biomarkers - Liang, Chuwen; Kan, Jun; Wang, Jingli; Lu, Wei; Mo, Xiaoyan; Zhang, Bei (Frontiers in Immunology, 2024)
Nasopharyngeal carcinoma (NPC) is a neoplasm related to inflammation; the expression of cytokines, such as CCL3, CCL4, CCL20, IL-1α, IL-1β, IL-6, IL-8, and IL-10, among others, is presumed to be associated with NPC occurrence and development. Therefore, the circulating levels of these cytokines may be potential biomarkers for assessing tumor aggressiveness, exploring cellular interactions, and monitoring tumor therapeutic responses. Numerous scholars have comprehensively explored the putative mechanisms through which these inflammatory factors affect NPC progression and therapeutic responses. Moreover, investigations have focused on elucidating the correlation between the systemic levels of these cytokines and the incidence and prognosis of NPC. This comprehensive review aims to delineate the advancements in research concerning the relationship between inflammatory factors and NPC while considering their prospective roles as novel prognostic and predictive biomarkers in the context of NPC.